2020
DOI: 10.1155/2020/6738532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Tuberculosis among Adult Household Contacts of Smear Positive Pulmonary Tuberculosis Patients Treated in Public Health Facilities of Haramaya District, Oromia Region, Eastern Ethiopia

Abstract: Background. Tuberculosis is an infectious airborne disease caused by Mycobacterium tuberculosis. It still remains a major public health problem which affects all age groups. Risk of exposure is higher in household contact than members of the general population. Objective. The aim of this study was to assess the prevalence and associated factors of tuberculosis among adult household contacts of smear positive pulmonary tuberculosis in Haramaya district, Oromia Region, Eastern Ethiopia from February to March, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
(21 reference statements)
3
16
0
2
Order By: Relevance
“…The better the quality of lighting in the house, the less likely the incidence of pulmonary tuberculosis. These results align with Eastern Ethiopia research; places' lighting status associate with pulmonary tuberculosis 26 . Persistent with Aceh Besar District's findings, there was a significant correlation between the lighting condition and pulmonary tuberculosis incidence.…”
Section: Discussionsupporting
confidence: 88%
“…The better the quality of lighting in the house, the less likely the incidence of pulmonary tuberculosis. These results align with Eastern Ethiopia research; places' lighting status associate with pulmonary tuberculosis 26 . Persistent with Aceh Besar District's findings, there was a significant correlation between the lighting condition and pulmonary tuberculosis incidence.…”
Section: Discussionsupporting
confidence: 88%
“…Its prevalence among contacts was 1.2% (microbiologically proven TB), 51.5% of latent TB and 3.4% of MDR or XDR TB; in contrast, among high-income settings, there were 28.1% LTB among contacts [6]. A study conducted in Ethiopia also showed that the overall prevalence of pulmonary tuberculosis among adult household contacts was 7.8% [7].…”
Section: Introductionmentioning
confidence: 99%
“…The case burden of TB is higher in Ethiopia (177/100,000 population) than that of the average case burden of TB worldwide (133/100,000) [3,6]. Social and behavioral factors including smoking, drinking alcohol, drinking raw milk, having a family history of tuberculosis, living in poor ventilated and inadequate size room, and rural residence are among risk factors hastening the disease progress [7][8][9]. On the other hand, an estimated 81 million Ethiopian populations are dwelling in endemic areas of the IPIs [10].…”
Section: Introductionmentioning
confidence: 99%